Нефтевытесняющая композиция на основе тройной системы ГЭР - Шолидодов, Мехроб Рустамбекович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
This paper presents the results of studies of the phase diagrams of the binary systems "boric acid - glycerol", "boric acid - urea" and "glycerol - urea", which form the basis of the acid chemical composition for enhanced oil recovery. The fusibility diagram was studied by the capillary method. As a result of the study, it was found that the system glycerol - urea has the lowest eutectic.